Impact of body mass index on the efficacy of treatment modalities in women with refractory overactive bladder - Po-En Liu; Jiun-Chyi Hwang; Tsung-Hsien Su; Hui-Hsuan Lau (Scientific Reports)
Abstract Overactive bladder (OAB) is a prevalent condition that substantially impairs quality of life. Obesity and overweight status are recognized as significant risk factors for OAB, but their influence on treatment efficacy is not well understood. This cross-sectional study was conducted from January 2023 to October 2024 at a tertiary care hospital. Women diagnosed with refractory OAB were classified into normal weight, overweight, and obese groups according to their body mass index (BMI). Treatment options included combination pharmaceutical therapy and Botulinum toxin injections. Outcomes were assessed using the Overactive Bladder Symptom Score (OABSS) and quality of life questionnaires, administered before and 12 weeks after treatment. A total of 197 women were included in the study. Normal weight women demonstrated significant improvements in OAB symptoms and quality of life following both combination therapy and Botulinum toxin injection. Conversely, overweight and obese women showed limited improvement with pharmaceutical therapy but responded better to Botulinum toxin injections. The findings suggest that Botulinum toxin injection may be a more effective treatment modality for overweight or obese women with refractory OAB compared to pharmaceutical therapy. Normal weight women might benefit from initiating treatment with combination medication therapy.